Sensemaking in Leadership Communication Practices to Maintain Environmental Security in Ketapang Subdistrict, Tangerang City - Ayu Indah Lestari; Veranus Sidharta; Wenny Maya Arlena; Ahmad Zakki Abdullah; Ismail Alif (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study aims to understand how sensemaking operates within the leadership communication practices of neighborhood leaders (RT heads) in maintaining environmental security in Ketapang Subdistrict, Tangerang City. Employing a descriptive qualitative approach with a case study design, data were collected through semi-structured interviews with two RT heads actively involved in community security efforts. Thematic analysis was conducted using NVivo software to map communication patterns and the formation of social values. The findings reveal that RT heads construct sensemaking by framing security threats based on their contextual realities, ranging from social issues like drug abuse to structural challenges such as inadequate public facilities. These interpretations inform the communication strategies and channels, including digital tools and face-to-face engagement. Furthermore, participatory decision-making processes produce technical responses and cultivate social values such as collective responsibility, information ethics, and anti-vigilantism. This study contributes to developing sensemaking theory in community leadership contexts and offers practical recommendations for local leaders in building participatory, value-based security systems. The research emphasizes the importance of contextual, inclusive, and ethical leadership communication in strengthening social cohesion and resilience at the grassroots level.